Ritual as reflected by censorship. The Control Bureau as the custodian of the cultural image of the authorities in the early days of the People’s Republic of Poland - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The ritual as a series of actions specified by traditions or a given political system, defined in detail and repeatable, was also fulfilled in the communist system. There it was aimed at introducing and amalgamating the order imposed on Poland by the Soviets after WWII. It could only be achieved by strictly observing the rules of Socialist rites. And that did not only apply to, however important, the celebrations of holidays according to the communist calendar, but also to the master principles which the enforcers of the new order used towards society. The indicated research material, extracted from censorship archives, shows that regardless of the changing media policy in the first decade after WWII, from the very beginning there existed invariable rules which constituted a compass for specific choices: the ban on criticising or disturbing the good name of the authorities, starting with Generalissimo Stalin, through the leaders of the states subordinate to him, higher-ranking officials, police and the army, to udarniks. The Control Bureau for Press, Publications and Performances was one of the most active bodies in the field. In the privacy of their offices, without the publicity so common for the clamorous ceremonies and rallies, censors worked to maintain the Stalinist rituals.